Giant Metrewave Radio Telescope detection of associated H i 21-cm absorption at z = 1.2230 towards TXS 1954+513. Issue 4 (5th November 2016) - Aditya, J. N. H. S.; Kanekar, Nissim; Prochaska, J. Xavier; Day, Brandon; Lynam, Paul; Cruz, Jocelyn
Abstract: We have used the 610-MHz receivers of the Giant Metrewave Radio Telescope (GMRT) to detect associated H i 21-cm absorption from the z = 1.2230 blazar TXS 1954+513. The GMRT H i 21-cm absorption is likely to arise against either the milliarcsecond-scale core or the one-sided milliarcsecond-scale radio jet, and is blueshifted by ≈328 km s −1 from the blazar redshift. This is consistent with a scenario in which the H i cloud giving rise to the absorption is being driven outwards by the radio jet. The integrated H i 21-cm optical depth is (0.716 ± 0.037) km s −1, implying a high H i column density, N_HI = (1.305 ± 0.067) × ( T_s/100 K) × 10^20 cm −2, for an assumed H i spin temperature of 100 K. We use Nickel Telescope photometry of TXS 1954+513 to infer a high rest-frame 1216 Å luminosity of (4.1 ± 1.2) × 10 23 W Hz −1 . The z = 1.2230 absorber towards TXS 1954+513 is only the fifth case of a detection of associated H i 21-cm absorption at z > 1, and is also the first case of such a detection towards an active galactic nucleus (AGN) with a rest-frame ultraviolet (UV) luminosity ≫10 23 W Hz −1, demonstrating that neutral hydrogen can survive in AGN environments in the presence of high UV luminosities.